2009
DOI: 10.1590/s1413-35552009005000015
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas musculoesqueléticos em eletricistas de rede de distribuição de energia

Abstract: Background: Linemen should be evaluated regarding the presence of musculoskeletal symptoms to guide the identification of risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…Majority of the studies have reported that the prevalence and incidence rate of WRMDs was purely based on data source surveillance [4,[9][10][11]. There was only one study that has been conducted as an on-field clinical surveillance by using a validated screening questionnaire such as the McGill questionnaire to identify the prevalence and incidence rate of WRMDs among the lineman profession [2]. Therefore, one might argue that credibility of the reported results on the prevalence of WRMDs among linemen is questionable.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Majority of the studies have reported that the prevalence and incidence rate of WRMDs was purely based on data source surveillance [4,[9][10][11]. There was only one study that has been conducted as an on-field clinical surveillance by using a validated screening questionnaire such as the McGill questionnaire to identify the prevalence and incidence rate of WRMDs among the lineman profession [2]. Therefore, one might argue that credibility of the reported results on the prevalence of WRMDs among linemen is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar retrospective study conducted in the USA, a high risk of back strain has been found among linemen who required time off from the office after the injury [9]. Meanwhile, a study conducted in China has reported a high prevalence of low back (63%) and shoulder (43%) musculoskeletal symptoms among linemen [2]. Furthermore, a surveillance report from electric utility companies has described a high incidence rate -includes a study population of linemen/lineman/line workers or power line workers, -includes measurement of the incidence or prevalence rate of musculoskeletal disorders among this population, -provides information on methodological issues on the measurement of job tasks analysis associated with the development of musculoskeletal disorders among linemen, -includes data on measurement of predictive risk factors of WMSDs due to job tasks analysis.…”
Section: Pattern Of Various Wrmds Among Linemenmentioning
confidence: 99%
See 3 more Smart Citations